EXPLORING THE POTENTIAL OF ASTROTOURISM: A SUSTAINABLE NICHE IN MODERN TRAVEL - Sharma, Vandana; Bumra, Chinu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Astrotourism, a subset of tourism that focuses on stargazing and astronomy activities, is gaining popularity as people become more interested in science, nature, and sustainability. This article investigates the factors that attract tourists to India for astrotourism. It also showcases successful examples from countries such as India. Astrotourism not only benefits local economies, but it also raises environmental awareness. As dark skies become scarcer, conserving them through responsible tourism becomes critical. This study aims to understand tourist preferences, destination strengths, and how India can improve and promote astrotourism more effectively.